Iatrogenic heart injuries - Filgueira, José Luis (Cirugía del Uruguay, 1973)
This subject is little treated in the literature, however its knowledge presents great practical interest, both for the technician who is carrying out a procedure capable of determining this complication, as well as for the surgeon who is consulted to resolve it.